Root canal treatment of maxillary second premolar with three roots and three canals: clinical cases - Alper Kustarci; ER Kürsat; Kerem Engin Akpinar (Universidade Estadual de Campinas, 2016)
An accurate diagnosis of the anatomy of the root canal system is a prerequisite for successful root canal treatment. According to the endodontic literature, maxillary second premolars usually have one root and one canal. The possibility of three roots and three canals in maxillary second premolars is quite small. Diagnostic means such as preoperative radiographs and examination of the pulp chamber floor aid the location of root canal orifices. The aim of this clinical article is to describe the unusual anatomy that was detected in two maxillary second premolars during routine endodontic treatment.